Molecular dynamics study on structure evolution of monocarboxylic acid intercalated layered double hydroxides. Issue 101 (17th October 2016) - Tong, Xuhang; Choi, Phillip; Li, Shuang; Shi, Yixiang; Zhang, Hao
Abstract : Classical molecular dynamics simulations were conducted to investigate the atomistic structures of monocarboxylic acid intercalated LDHs – a promising candidate for solid sorbents for carbon dioxide capture at intermediate temperatures. Abstract : Hydrotalcite derived materials are considered to be promising candidates for solid sorbents for carbon dioxide capture at intermediate temperatures (250–400 °C). The recently developed organically intercalated layered double hydroxide (LDH) shows a great improvement in carbon dioxide adsorption capacity compared to alternative sorbents. However, the molecular-scale structure of this new class of materials is yet to be understood, hindering the further development of high-capacity carbon dioxide adsorbents based on LDH. In the current study, classical molecular dynamics simulations were conducted to investigate the atomistic structures of monocarboxylic acid intercalated LDHs containing Mg and Al in the ratio 3 : 1. The replacement of carbonate anions by stearate anions (CH3 (CH2 )16 COO − ) in LDH expanded the basal spacing from 7.8 Å to 19.6 Å. The presence of water molecules could further increase the basal spacing to up to 33.5 Å. In addition, the basal spacing of LDH could be expanded by other carboxylic anions ( e.g., CH3 (CH2 )11 COO −, CH3 (CH2 )5 COO − ), and the spacing was proportional to the length of the carbon chains. Water molecules inside interlayer galleries tend to bond firstly with the hydroxyl groups of hydroxide layers, and water molecules added subsequently then fill the gallery space. For comparison, LDHs intercalated by CH3 (CH2 )16 COO − and CH3 (CH2 )6 COO − were prepared by the acid-aided anion-exchange method and characterized by powder X-Ray Diffraction (XRD) analysis, thermogravimetry (TGA) and Differential Scanning Calorimetry (DSC). The basal spacing and XRD patterns observed in the simulations are in good agreement with experimental observations. The quantitative analyses in this work could provide guidelines for optimizing the lamellar structure of LDH to improve its capacity for CO2 capture.